Determination of the term “Government official” in the Context of the United Nations Convention against Corruption - Zharovska, Halyna; Yushchyk, Olena; Bodnaruk, Oleksandr; Toma, Marianna; Gusar, Lesia (Revista San Gregorio, 2020)
The article deals with the problems of determining the concept of “public official” and definiteness of terms in the context of enforcement of the United Nations Convention against Corruption. The author carried out the analysis of the specified category, identified its attributes and features of the international legal enshrinement both in the text of the Convention, and in the text of other international legal acts in the field of anti-corruption, mainly of regional value. It is established that the definition of “government official” unified by the Convention makes it possible to clearly and unambiguously determine the range of subjects of corruption to which international legal influence of not only the Convention itself, but also the corresponding coordinated activities of international anticorruption institutions and national governments of the states ratifying the Convention applies. At the same time, it is proved that there is a distinction between the concepts of “official” and its separate special type – “government official” at the level of international legal regulation, which is a shortcoming of the Convention. In particular, it is established that the Convention is limited by the category of only those civil servants who hold positions in public authorities financed from the state budget and perform state functions only. In this context, it is concluded that there is a need for significant terminological clarification of the legal regulation provided by the Convention through the implementation of the category of “local self-government officials”.
Keywords: Corruption Offenses, Government Official, Public Authority Official, Public Governance, Public Administration, UN Convention against Corruption